Book Reviews. - Leemans, Johan; van den Eynde, Sabine; Slattery, Joseph A.; Prior, Michael; McNamara, Martin; Reinhartz, Adele; Questier, Michael; Swanson, R. N.; Hinwood, Bonaventure; Hamilton, Alastair; Louth, Andrew; Marett-Crosby, Anthony; et al. (Heythrop Journal, 2001)
Books reviewed: John H. Hayes (ed), Dictionary of Biblical Interpretation Fernando F. Segovia and Mary Ann Tolbert (eds), Teaching the Bible: The Discourses and Politics of Biblical Theology John N. Oswalt, The Book of Isaiah Chapters 40–66 Jerome D. Quinn and William C. Wacker, The First and Second Letters to Timothy. A New Translation with Notes and Commentary Brian E. Daley, On the Dormition of Mary: Early Patristic Homilies Mary Clayton, The Apocryphal Gospels of Mary in Anglo-Saxon England Daniel Boyarin, Dying for God: Martyrdom and the Making of Christianity and Judaism Brad S. Gregory, Salvation at Stake: Christian Martyrdom in Early Modern Europe Sara Lipton, Images of Intolerance: The Representation of Jews and Judaism in the ‘Bible moralisée’ Zachary Hayes, Bonaventure: Mystical Writings N. J. G. Pounds, A History of the English Parish: The Culture of Religion from Augustine to Victoria J. L. Heilbron, The Sun in the Church: Cathedrals as Solar Observatories Edelgard E. DuBruck and Barbara I. Gusick (eds), Death and Dying in the Middle Ages Christopher Tyerman, The Invention of the Crusades Jaroslav Folda, The Art of the Crusaders in the Holy Land, 1098–1187 Marguerite Porette, The Mirror for Simple Souls Peter Fergusson and Stuart Harrison, Rievaulx Abbey: Community, Architecture, Memory Jennifer Loach, Edward VI John A. Vickers (ed), A Dictionary of Methodism in Britain and Ireland John Henry, The Scientific Revolution and the Origins of Modern Science Ronald L. Numbers and John Stenhouse (eds), Disseminating Darwinism: The Role of Place, Race, Religion, and Gender Jeffrey M. Burns, Disturbing the Peace: A History of the Christian Family Movement, 1949–1974 Leonardo Boff, The Maternal Face of God: The Feminine and its Religious Expressions Curtis L. Hancock and Brendan Sweetman, Truth and Religious Belief: Conversations on Philosophy of Religion Louis Greenspan and Stefan Andersson (eds), Russell on Religion Richard Buxton (ed), From Myth to Reason? Studies in the Development of Greek Thought John A. Palmer, Plato's Reception of Parmenides S. R. Slings, Plato: ‘Clitophon’ Keimpe Algra, Jonathan Barnes, Jaap Mansfeld and Malcolm Schofield (eds), The Cambridge History of Hellenistic Philosophy Michael Inwood, Heidegger (Past Masters) P. H. Coetzee and A. P. J. Roux (eds), The African Philosophy Reader D. Z. Phillips, Philosophy's Cool Place Oliver Leaman (ed), The Future of Philosophy: Towards the Twenty-First Century Audrey R. Chapman, Unprecedented Choices: Religious Ethics at the Frontiers of Genetic Science (Theology and the Sciences series)